High purity pressurised hydrogen production from syngas by the steam-iron process. Issue 58 (2nd June 2016) - Voitic, Gernot; Nestl, Stephan; Malli, Karin; Wagner, Julian; Bitschnau, Brigitte; Mautner, Franz-Andreas; Hacker, Viktor
Abstract : The production of high purity hydrogen out of a syngas feed is achieved with the steam-iron process at elevated pressure. Abstract : The production of hydrogen in a fixed bed reactor at a maximum pressure of 50 bar by oxidising an oxygen carrier (Fe2 O3 /Al2 O3 /CeO2 ) with 0.06 g min −1 of steam at 1023 K is discussed. Reductions were performed with synthesis gas at ambient pressure and 1023 K for 90 minutes. The influences of the elevated system pressure on the carbon contamination, the quantification of the contaminations in the produced hydrogen and the oxygen carrier conversion are analysed. The results show that small amounts of carbon depositions are formed during the reduction, which are re-oxidised with steam leading to the contamination of the hydrogen. The hydrogen purity obtained in the experiments is within the range of 99.958% to 99.999% with CO as the main impurity. The amount of contaminations as a result of the oxidation of the solid carbon is not influenced by the elevated system pressure, which confirms the suitability of the reformer steam-iron process in a fixed bed to produce pressurised hydrogen directly from a hydrocarbon feed. The oxygen carrier conversion displays an initial drop followed by a slightly linear decrease. Air-oxidations revealed a regeneration effect on the oxygen carrier conversion, which reversed a part of the conversion losses.